Ecotourism, Women, and Development: Reflections on the Women’s Participation in Tourism in Protected Areas in Colombia - Ariza Marín, Leidy Johana; Bolaños Briceño, Jorge Arturo (Universidad Pedagógica y Tecnológica de Colombia, 2020)
This article presents some reflections on the involvement of women as users and providers of tourism services in protected areas and highlights the importance of female travelers as a growing segment of the market. It also delves into the experience of female travel, analyzing its motivations and impact on the inequalities in the use of space. Considering that protected areas in the country are frequently inhabited by marginalized and vulnerable communities—either because of the armed conflict or because of limited opportunities—, the article emphasizes the importance of women’s work in the ecotourism sector and its multiplier effect on the well-being of local communities. In addition, it proposes a scenario of gender-oriented ecotourism promotion from a local construction perspective, in which ecotourism potential is combined with the skills and strengths of all local actors as a whole. Using a qualitative, non-experimental, and exploratory methodological approach, a literature review is carried out, including institutional documents and research on the management of ecotourism in protected areas; its social, economic and environmental implications; and the participation of women in tourism services, both as providers and users.